Electronic media studies in upgrading learning and teaching: effective strategy provided by RTM - Mokhtar Muhammad; Haliza Hasan; Aeyneda Zairyn Abdul Jalil; Nur Aziemah Mohd Azman; Raja Putri Nadiah Raja Ahmad; Mardhiyah Mohammed Zin (Penerbit Universiti Kebangsaan Malaysia, 2020)
Listening to the radio is one of the mediums of communication that is still popular among Malaysians, no matter the age or gender or economic status. It is the choice of all segments of society as it is relevant to our daily lives. However, most Malaysian listeners still preferred listening to the Top Five private radio stations such as Hot FM, Suria FM and ERA FM as compared to RTM-owned ones. The listeners’ perception is the main factor that is closely aligned with the acceptance and popularity of radio stations. This study used the quantitative research method to analyze the factors that contribute to the effectiveness of radio stations provided by Radio Television Malaysia (RTM) among listeners in Klang Valley. It focused on 130 respondents residing around the Klang Valley area. The variables tested in this study include perception, acceptance, radio deejays (DJs), radio content, songs, and promotion. As a result, radio station DJs are the main factor that influences the effectiveness of radio stations provided by RTM. In conclusion, the results from this study will help improve RTM’s services and quality to increase the listeners’ interest in the radio stations through the identification of the factors that contribute to the effectiveness of radio stations among the listeners in the Klang Valley area.